Correlation between body image physical activity and sleep duration with nutritional status teaching-students at the University of Darussalam Gontor for girls - Safira Kholifatul Ummah; Kartika Pibriyanti; Fathimah Fathimah (Universitas Darussalam Gontor, 2020)
Background: Malnutrition both overweight and malnutrition in children and adolescents often occur in developing countries. At this time many factors affect the nutritional status of adolescents including physical activity, psychological aspects (body image) and sleep duration. Objective: This study aims to determine the risk factors associated with the nutritional status of teaching-students at the University of Darussalam Gontor. Method: This research is an observational survey research with cross-sectional study design. Research subjects were 94 teaching-students 18-21 years old at the University of Darussalam Gontor For Girls. Statistical tests use the Gamma correlation test to determine the relationship between independent variables and dependent variables. The results of this study indicate that there was a significant correlation between body image and nutritional status (p = 0.030) and there was no significant correlation between physical activity (p = 0.385) and sleep duration (p = 0.156) with nutritional status.Keyword : Nutritional Status, Body Image, Physical Activity, Sleep Duration, Teaching Students Latar Belakang: Malnutrisi baik kelebihan berat badan dan gizi buruk pada anak-anak dan remaja sering terjadi di negara-negara berkembang. Pada saat ini banyak faktor yang mempengaruhi status gizi remaja termasuk aktivitas fisik, aspek psikologis (citra tubuh) dan durasi tidur. Tujuan: Menganalisis faktor risiko yang terkait dengan status gizi mahasiswi guru di Universitas Darussalam Gontor. Metode: Penelitian ini adalah penelitian survei observasional dengan desain studi cross-sectional, uji hipotesis statistik yang digunakan adalah Uji Korelasi Gamma. Subjek penelitian adalah 94 mahasiswi guru berusia 18-21 tahun di Universitas Darussalam Gontor Kampus Putri. Tes statistik menggunakan uji korelasi Gamma untuk menentukan hubungan antara variabel independen dan variabel dependen. Hasil penelitian ini menunjukkan bahwa ada hubungan yang signifikan antara citra tubuh dan status gizi (p = 0,030) dan tidak ada hubungan yang signifikan antara aktivitas fisik (p = 0,385) dan durasi tidur (p = 0,156) dengan status gizi.Kata kunci : status gizi, body image, aktifitas fisik, durasi tidur, mahasiswi guru.